The Effect of Learning Process Establishment on the Development to the Health-Promoting School: A Case Study of a School under Border Patrol Police Bureau - Chansawang, Wannee; Jittanoon, Piyanuch; Saksorngmuang, Pimpisa (Journal of Health Science of Thailand, 2017)
The objective of this study was to determine the effect of learning process establishment on the development to a health-promoting school. The study setting was schools which had not yet been granted health-promoting school status. One school under border patrol police bureau was purposively selected based on the determination of its administrative team to improve the school condition to meet the criteria of health-promoting school. The study instrument was the learning process establishment for health-promoting school development which was comprised of three major stages; 1) preparation stage, prioritizing on understanding the concept and the process of health-promoting school development and exchanging experience with and learning from schools approved as gold medal health-promoting school, 2) learning stage, emphasizing on learning from actual practice regarding the process of health-promoting school development, and 3) evaluation stage, focusing on the outcome of the development in which the school was assessed according to the health-promoting school criteria. Supportive data was collected after the completion of learning process establishment from interviews with school administrative and health teacher, observation, and review of document relating to the development and evaluation outcome. The data was validated using triangulation method and analyzed using content analysis. The results revealed that after the application of learning process establishment, the scores of the school on all health-promoting school components were higher than those before the introduction of learning process establishment. The level of all health-promoting school components were at a very good level and the school has been approved by the district evaluation committee to be a gold medal health promoting school.